1990
DOI: 10.1152/ajpgi.1990.258.1.g96
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of cholera toxin with cloned human goblet cells in monolayer culture

Abstract: Exposure of the intestinal mucosa to Vibrio cholerae enterotoxin (CT) results in mucus secretion from intestinal goblet cells. On the other hand, there is evidence that elevation of intracellular adenosine 3',5'-cyclic monophosphate levels is not sufficient to induce rapid mucin secretion. To determine whether CT has direct effects on human goblet cells and whether CT alone can elicit rapid exocytosis of apical mucin granules, purified CT was applied to monolayer cultures of well-differentiated HT-29-18 N2 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 0 publications
1
23
1
Order By: Relevance
“…Previous studies of the colonization process have indicated that only gram-negative bacteria aggregate in the mucus (35) and that only V. fischeri sets up permanent residence in the crypt spaces (24). Taken together, these data indicate that the colonization of the E. scolopes light organ is a process of ever-increasing specificity.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Previous studies of the colonization process have indicated that only gram-negative bacteria aggregate in the mucus (35) and that only V. fischeri sets up permanent residence in the crypt spaces (24). Taken together, these data indicate that the colonization of the E. scolopes light organ is a process of ever-increasing specificity.…”
Section: Discussionsupporting
confidence: 51%
“…In pathogenic associations, bacteria and bacterial products, such as cell surface molecules and toxins, have been implicated in the control of mucus secretion at both the cellular and molecular levels (12). For example, in the pathogenesis of Vibrio cholerae, cholera toxin triggers mucin release from cultured human goblet cells (16,24) and rat colonic tissue (7). In the lungs of patients suffering from cystic fibrosis, excess mucus secretion leads to creation of an environment that is conducive to persistent colonization by Pseudomonas aeruginosa (5,27).…”
mentioning
confidence: 99%
“…It contains an active TATA box, binds ATF-1 and Sp1 transcription factors, and is activated by cAMP-dependent protein kinase and PKC signaling pathways. In this report we showed that CTA, which has already been shown to activate mucin secretion in colon cancer cell (43), is capable of specifically inducing MUC5B promoter activity in KATO-III but not in AGS cells. Thus, we can postulate that MUC5B promoter activation via cAMP signaling in KATO-III cells involves activation of adenyl cyclase through activation of G s regulatory proteins.…”
Section: Discussionmentioning
confidence: 51%
“…Vibrio cholerae enterotoxin, by increasing intracellular adenosine 3Ј,5Ј-cyclic monophosphate, increases mucus secretion from intestinal goblet cells both in vitro and in vivo (14,32,40,41). The wild-type L. monocytogenes strain EGD increases mucus secretion in vivo (63), with the result that listeriolysin O toxin promotes the increased production of secreted and membrane-bound mucins and the upregulation of MUC genes in cultured mucin-secreting HT29-MTX cells (6,7,47).…”
Section: Discussionmentioning
confidence: 99%